Enhancement of Vaccinia Virus Based Oncolysis with Histone Deacetylase Inhibitors - MacTavish, Heather; Diallo, Jean-Simon; Huang, Baocheng; Stanford, Marianne; Le Boeuf, Fabrice; De Silva, Naomi; Cox, Julie; Simmons, John Graydon; Guimond, Tanya; Falls, Theresa; McCart, J. Andrea; Atkins, Harry; et al. (PLOS ONE, 2011)
Histone deacetylase inhibitors (HDI) dampen cellular innate immune response by decreasing interferon production and have been shown to increase the growth of vesicular stomatitis virus and HSV. As attenuated tumour-selective oncolytic vaccinia viruses (VV) are already undergoing clinical evaluation, the goal of this study is to determine whether HDI can also enhance the potency of these poxviruses in infection-resistant cancer cell lines. Multiple HDIs were tested and Trichostatin A (TSA) was found to potently enhance the spread and replication of a tumour selective vaccinia virus in several infection-resistant cancer cell lines. TSA significantly decreased the number of lung metastases in a syngeneic B16F10LacZ lung metastasis model yet did not increase the replication of vaccinia in normal tissues. The combination of TSA and VV increased survival of mice harbouring human HCT116 colon tumour xenografts as compared to mice treated with either agent alone. We conclude that TSA can selectively and effectively enhance the replication and spread of oncolytic vaccinia virus in cancer cells.